Saint Rita - Matilde Bernabei; Lux Vide (Italy Lux Vide, 2011)
A biographical religious film depicting the life of Saint Rita of Cascia, focusing on her faith, suffering, marriage, widowhood, and eventual devotion to religious life, highlighting themes of forgiveness, perseverance, and Christian spirituality.
Italian religious drama film based on the life of Saint Rita of Cascia.
General audience.
Keywords: 9; Christian saints